Investigating accountability of state subsidies for political parties - Kurniawati, Chandra Puspita; Sandha, Oktarika Ayoe; Suntharanurak, Sutthi; Muhtar, Entang Adhy; Pancasilawan, Ramadhan (Badan Pemeriksa Keuangan Republik Indonesia, 2023)
Regulations stipulate that a political party must prepare financial reports to facilitate sound financial management and accountability of the state subsidies it receives. However, its accountability remains problematic, raising a question: How do the related policies deal with the accountability of state subsidies for political parties? This study aims to evaluate issues related to accountability in the policies governing the management of state subsidies for political parties. This study is normative legal research. Within a meta-analysis framework, critical analysis of the relevant policies in the form of laws and regulations and other reliable sources of information is carried out. The study finds that the policies provide rules to ensure eligible political parties’ right to obtain state subsidies and employ audit and administrative sanctions to enhance state subsidy accountability. Nevertheless, the policies still overlook important issues related to vertical accountability of political parties and government, horizontal accountability of government, internal control mechanisms, supervision requirements, and formal and material responsibilities by relevant in-charge parties. Moreover, the running audit practices do not provide much value for improvement. This study provides policy-makers with a new perspective on relevant studies so that the government will consider the comprehensive management of state subsidies for political parties by relevant in-charge parties before elevating the value of the subsidies.